Economic Efficiency of Crops in The Negru Vodă Area, Dobrogea Region, Romania - Liliana MIRON; Elena DOROFTEI; Grigore-Valentin BELENIUC (Communications of International Proceedings, 2023)
The purpose of the work was to determine the economic efficiency of wheat, barley, rapeseed, sunflower and pea crops, located in the conditions of the Negru Vodă area. The crops of wheat, barley, rape, sunflower and peas were harvested at Negru Vodă and Cerchezu village, Dobrogea region, Romania. The agricultural area is 153.73 ha. In the 2020-2021 agricultural year, the following were cultivated: wheat - 40 ha, barley - 29.25 ha, sunflower - 47.7 ha, rapeseed - 28.78 ha and peas - 8.0 ha. The economic results of the wheat crop at an average production of 683 kg/ha, with 3102.10 lei costs/ha, having a harvest utilization price of 0.76 lei/kg, no profit was obtained but a loss of 2583.02 lei. The total costs for barley culture were in the amount of 3239.69 lei, at the production of 1213 kg/ha, with a capitalization price of 0.745 lei/kg, an income of 903.69 lei/ha was obtained. For rapeseed culture the value of the production was 2461.37 lei/ha, exceeding the costs by 573.81 lei/ha, obtaining in this case a profit. The sunflower resisted the drought and an average production of 2668 kg/ha was obtained. Since the utilization price of the sunflower was 2,247 lei, the value of production/ha was 5,995 lei considering the costs of 2411.94 lei/ha, a profit of 3583.06 lei/ha was achieved. Peas occupied an area of 8 ha in 2021 but culture was totally compromised, so the mechanization costs for the establishment of the crop were 770 lei/ha and with the seed 374 lei/ha. In order to co-interest farmers, the value of prices of agricultural products should be reconsidered.
Keywords: economic efficiency; wheat; barley; rapeseed; sunflower; pea crop; Negru Voda area